EXPERIENCE OF USING JAMBOARD IN DISTANCE LEARNING OF MATHEMATICAL DISCIPLINES - Varyvoda , Viktoriia; Hryshko , Olena; Oliynyk , Oleh Petrovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
This article is devoted to the possibilities of using the online Google Jamboard in the organization of the process of teaching mathematical disciplines in the conditions of remote learning. The main advantages and disadvantages of this digital tool are analyzed.